Evaluation of different soil and water conservation measures suitable for expressway construction in arid areas in northwest China. Issue 4 (20th April 2020) - Liu, Tao; Cheng, Jinhua; Zhang, Hongjiang; Zhao, Kun; Lu, Xudong; Wang, Ti; Li, Hongjun; Chen, Lin
Abstract: In order to determine the most efficient soil and water conservation measure for different engineering units, the volume weight of soil (VWS), soil water content (SWC), soil porosity, soil erosion resistance (SER), anti-scour coefficients (ASC), and vegetation coverage of 12 protective measures and four unprotected measures were investigated. In addition, 16 water conservation measures were evaluated using the gray correlation method. Our results suggest that SWC, SER, ASC, and vegetation coverage of a square grid area were higher than those of other measures on the filling slope ( p < 0.05). However, in the excavated slope, SWC, SER, ASC, and vegetation coverage of the unprotected measures area were higher than those in the protected measures ( p < 0.05). Our results also indicate that the gray comprehensive evaluation value of arch framework measures in the fill slope and unprotected natural recovery measures of the excavated side slope were significantly greater than those of other measures ( p < 0.05). This finding indicates that the effect of soil and water conservation on these measures were better than others. Our findings provide an indication for the implementation of soil and water conservation measures for expressways situated in arid areas in China.